Two versus four sterile water injections for managing back pain in labour. (September 2022) - Lee, Nigel; Leiser, Mrs Bernadette; Halter-Wehrli, Ms Yvonne; Mårtensson, Lena B; Gao, Yu; Kildea, Sue
Abstract : Introduction: The efficacy and safety of sterile water injections to manage labour back pain was demonstrated in recent clinical trials. Varying the number of injections used in the procedure from four to two has been cited as a means of possibly reducing the injection pain while maintaining analgesic effect. However, it is not known if the pain relief provided by two sterile water injections is the same as that from the usual four injections, or if fewer injections results in a decrease in injection discomfort. Aim: The aim of this trial was to determine if the pain relief experienced by participants receiving two water injections would be clinically equivalent to four. Methods: We conducted a multicenter randomised controlled equivalence trial in which 238 women in labour with a Visual Analogue Scale pain score (VAS) of 70 millimetres (mm) (0= no pain; 100= worst pain imaginable) were randomised to two or four sterile water injections. The primary outcome was pain measured on a VAS at 30 minutes post treatment. A clinically relevant a-priori margin of equivalence was set at ±10 mm difference in VAS scores. Secondary outcomes included the likelihood of achieving an at least 30% and 50% reduction in pain, birth and neonatal outcomes. Results: Clinical equivalence was not demonstrated. Both techniques achieved an at least 30% reduction in pain in over 75% of participants though duration of effect was longer in the four injection group. There was no difference in other birth related secondary outcomes. Conclusion: Four injections provided a margin of benefit over two injections in level and duration of analgesia. Four injections remains the technique of choice though two injections still provided significant pain relief and would be suitable where it was not possible or desirable to provide four.